Marine microbial community taxonomic and functional indicators to volcanic and anthropogenic stressors in Deception Island, Antarctica - Duarte, Bernardo (2024)
In recent years, the growth in Antarctic tourism has stimulated research on the anthropogenic impacts on the region, boosted by advances in OMIC technologies applied to polar microbial communities. This study aimed to assess the human impacts on marine prokaryotic and viral communities of Deception Island by identifying potential taxonomic, functional, and resistome indicators of both anthropogenic and natural/volcanic pressures. Proteobacteria, Bacteroidetes, and Actinobacteria were the dominant phyla, with notable variations attributed to volcanic activity and anthropogenic pressure. The abundance of Euryarchaeota in regions with increased volcanic activity underlines their adaptability to extreme conditions. Their mercury resistance coupled with their ability to cope with toxic heavy metals is a critical component in managing volcanic mercury concentrations. Actinobacteria, Cyanobacteria, Planctomycetes, and Synergistetes showed distinctive abundance patterns with potential ecological implications related to volcanic environments. Functional analyses revealed the enrichment of functions associated with metal-based, hydrocarbon degradation, and nitrogen metabolism. Submarine volcanic vents contributed significantly to the shape of functional diversity. Identification of specific functions related to nosocomial infections and gastroenteritis highlights the impact of anthropogenic activities on functional traits. Antibiotic resistance genes (ARGs) showed nuanced patterns influenced by both anthropogenic pressure and volcanic activity. Actinobacteria were correlated with increased ARG abundance, which was enhanced by wastewater disposal. Remarkably, Fumarole Bay showed an increased prevalence of certain ARGs, despite a lower anthropogenic impact, suggesting a unique selective pressure induced by volcanic activity. The responsiveness of these indicators to varying levels of pressure characterizes them as valuable tools for assessing and mitigating anthropogenic impacts on the marine waters of Deception Island.